Analysis Shift Behavior Consumptive With The Presence of Digital Payment Platforms as Transaction Tools in Islamic Economics (Case Study of Pekanbaru City Society) - Nopa, Ika Yuliar; H, Hamdani; C, Chalirafi; I, Ichsan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research focuses on the problem of how the shift in consumer behavior with the presence of digital payment platforms as a transaction tool by the people of Pekanbaru City is reviewed based on Islamic economic views. The aim of this research is to determine the shift in consumer behavior with the presence of digital payment platforms as a transaction tool by the people of Pekanbaru city based on Islamic economic views. The method in this research is field research with a descriptive qualitative approach. This research was conducted using 3 techniques, namely observation, interviews and documentation. The research results found that the shift in consumption behavior of the people of Pekanbaru city was due to the ease of access to digital payments in the palm of their hands, following their desires to fulfill desires without considering the long-term benefits of the products purchased. The causes of people’s consumptive behavior are influenced by environmental factors, promotions or advertisements for a product, cashback, discounts and free shipping. Meanwhile, transactions on digital payment platforms, if viewed based on Islamic law, have different laws according to the contract used.